Sexual Health Knowledge among Malaysian with Coronary Artery Disease - Mansor, Wan Mazrizman Wan; Engkasan, Julia Patrick (Asian Journal of Health Research, 2025)
Introduction: Sexual counselling is a fundamental aspect of cardiac rehabilitation. It is challenging to develop an appropriate framework for sexual counselling in coronary artery disease patients without having knowledge about their level of sexual knowledge. Material and Methods: A descriptive, correlational cross-sectional study was conducted at the Cardiac Rehabilitation Clinic Universiti Malaya Medical Centre, Kuala Lumpur. A convenience sample of 112 patients diagnosed with myocardial infarction or coronary artery disease was recruited. The patient’s sexual health knowledge was assessed using the Sex After Myocardial Infarction Knowledge Test. Results: The majority of patients were male (85%), mean age of 57±11 years, Malay (46%), had secondary education (54%), married for 27±13 years and was diagnosed within 4±5 years. Questions on awareness of cardiac symptoms and safety during sexual activity scored the highest, while questions on medication safety, suitable time for sex, and partner communication scored the lowest. No statistically significant relationships found between the level of knowledge and age, sex, religion, education level, employment status, number of years of marriage, or duration of the diagnosis. Most of were interested in talking about sexual health but rarely had the opportunity to discuss. Conclusion: Sexual health is an important concern for patients with coronary artery disease. Some patients are symptomatic and have difficulty having sex. This study identifies specific issues that need to be addressed, especially convenient time, medication safety, and effective communication when providing sexual education.